EVIDENCE FOR ANISOTROPY IN CHLORINE NITROGEN INTERACTIONS IN THE CYANURIC CHLORIDE CRYSTAL-STRUCTURE - Maginn, S; Compton, R; Harding, M; Brennan, C; Docherty, R (1993)
The non-linearity of some of the chlorine/nitrogen intermolecular interactions upon which the known crystal structure of cyanuric chloride depends is evidence for the inadequacy of current isotropic models of interatomic potentials used for crystal packing predictions. © 1993.